SUSTAINABILITY AND ECONOMIC IMPACT OF CULINARY TOURISM: A STUDY OF FOOD TOURISM PRACTICES IN MUMBAI, MAHARASHTRA - Manoj Patkar, Prof. (Dr.) Gurdip Singh (Chelonian Research Foundation, 2025)
This paper examines the viability and economic benefit of culinary tourism in Mumbai, Maharashtra but especially makes an analysis on how local food has helped preserve both traditions and economic prosperity. The research relied on quantitative information of 240 tourists and 60 restaurant owners whereby the questionnaires and interviews employed by the study focused on six dimensions such as aspects of sustainability perceptions, spending patterns, and promotion of Maharashtrian cuisine. The analyses were done in terms of descriptive statistics, Pearson correlation, ANOVA, and multiple regression analysis with the help of SPSS v26 and Excel 365.The results indicate that two-thirds of the tourists pursue sustainable food choices and are more satisfied with the use of such practices. There was a high positive correlation (r = 0.68) between the amount of resources utilized by restaurant to sustain its operations and monthly revenue. Findings of the regression results were that sustainable practice and knowledge on local cuisine remarkably forecasts repeat visitation and tourist expenditure (R 2 = 0.57). The research paper finds that sustainable culinary tourism can not only contribute to cultural identity, but can make restaurants economically viable. Based on these insights, one can say the strategic marketing and a long-term integration of local food heritage should be promoted as part of tourism planning.